Unilateral Negative Myoclonus Caused by Herpes Simplex Virus Encephalitis - Jin-Mo Park; Jin-Sung Park; Yong-Won Kim; Ho-Won Lee; Da-In Lee; Sung-Pa Park; Hyun Seok Song (Journal of Movement Disorders, 2011)
Various neurologic manifestations of herpes simplex virus (HSV) encephalitis have been reported on the literatures. Chorea, ballism, choreoathetosis and myoclonus were reported as movement disorders which might be related with brain lesion by HSV encephalitis, but negative myoclonus (NM) has never been reported before. NM can be characterized as a shock-like involuntary jerky movement caused by a sudden, brief interruption of muscle activity. We experienced a case of HSV encephalitis with NM in unilateral arm and leg. In polygraphic monitoring, electroencephalography (EMG) silent periods are 50–250 ms in duration with no detectable EMG correlate.